2015
DOI: 10.1589/jpts.27.51
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aerobic exercise intensity on 24-h ambulatory blood pressure in individuals with type 2 diabetes and prehypertension

Abstract: [Purpose] To verify the effects of different intensities of aerobic exercise on 24-hour ambulatory blood pressure (BP) responses in individuals with type 2 diabetes mellitus (T2D) and prehypertension. [Subjects and Methods] Ten individuals with T2D and prehypertension (55.8 ± 7.7 years old; blood glucose 133.0 ± 36.7 mg·dL−1 and awake BP 130.6 ± 1.6/ 80.5 ± 1.8 mmHg) completed three randomly assigned experiments: non-exercise control (CON) and exercise at moderate (MOD) and maximal (MAX) intensities. Heart rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 45 publications
0
18
1
1
Order By: Relevance
“…Another aspect that can explain the differences between the present study and the one performed by Simao et al (20) is the intensity of the training session, since studies investigating PEH in individuals with diabetes (5-8), normotensive and hypertensive (9), and elderly (4) have suggested that exercises with higher metabolic and hemodynamic stress result in a greater and longer PEH. This happens as the result of a greater mechanical stress, and consequently, a greater release of vasoactive agents (4, 5, 7, 9).…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…Another aspect that can explain the differences between the present study and the one performed by Simao et al (20) is the intensity of the training session, since studies investigating PEH in individuals with diabetes (5-8), normotensive and hypertensive (9), and elderly (4) have suggested that exercises with higher metabolic and hemodynamic stress result in a greater and longer PEH. This happens as the result of a greater mechanical stress, and consequently, a greater release of vasoactive agents (4, 5, 7, 9).…”
Section: Discussioncontrasting
confidence: 79%
“…On the other hand, studies have highlighted that a single session of exercise can reduce blood pressure (BP) to below resting values in the elderly (4), individuals with diabetes (5-8), and both hypertensive (9) and normotensive (10) individuals. This phenomenon is known as post-exercise hypotension (PEH).…”
Section: Introductionmentioning
confidence: 99%
“…The beneficial effects of blood-pressure-lowering treatments on the risks of major cardiovascular events are well established10,11,12,13,14,15 ) ; however, the influence of health and fitness-related variables remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…This improvement might be due to increased peripheral vasodilatation and consequently, a decreased afterload following exercise and a reduction in the adrenergic efferent stimuli 21 , 22 ) . Aerobic exercise improves cardiorespiratory fitness in obese subjects with less cardiac workload as evidenced by the low myocardial oxygen consumption, while anaerobic exercise increases cardiac work and is difficult to maintain for extended periods of time 23 , 24 , 25 , 26 ) , Moreover, low-intensity aerobic exercise is less difficult, more easily tolerated, and can be practiced daily over an extended period of time.…”
Section: Discussionmentioning
confidence: 99%